Parroquia de Santa Águeda, Bogotá. Estudio de caso acerca de la educación para la construcción de paz (2019)
Peace is built upon actions that generate well-being, and education is conceived as one of the main activities through which welfare and new opportunities are created for people. Based on this premise, priest Germán Chaves from the Santa Águeda church has managed and directed a training process thought to improve the lives of community members by offering high quality and no cost education, including 34 academic projects involving courses, seminars, and certification programs, in a four year period, with a total of 2193 persons attending these courses. This article presents a case study of in the Santa Águeda community parish, an active subject that frames peace-building actions under community initiatives. The first section explains why a case study is applied to the understanding of this specific situation. Then, the authors examine theories about peace building that support the actions undertaken in the Santa Águeda parish. The third section presents the perception of the beneficiaries regarding these activities. Finally, the data and appreciations collected during field work in the parish are analyzed.